CTNI-47. INTERIM RESULTS OF NCT03011671: A MULTI-INSTITUTIONAL PHASE I STUDY OF ACETAZOLAMIDE WITH TEMOZOLOMIDE IN ADULTS WITH NEWLY DIAGNOSED MGMT-METHYLATED MALIGNANT GLIOMA. (12th November 2021) - Yamini, Bakhtiar; Lyne, Seán; Driscoll, Riley; Bernal, Giovanna; Wu, Longtao; NIcholas, Martin; Chmura, Steve; Collins, John; Park, Deric; Pytel, Peter; Karrison, Theodore; Stupp, Roger; et al.
Abstract: Preclinical studies indicate that up-regulation of carbonic anhydrase (CA) by temozolomide (TMZ), via a mechanism requiring the proto-oncogene BCL-3, promotes resistance to therapy in glioblastoma (GBM) cells. Moreover, the CA inhibitor, acetazolamide (ACZ), sensitizes patient-derived GBM cells and xenografts to TMZ. These findings led to the current Phase I study investigating the safety and efficacy of adding ACZ to adjuvant TMZ in patients with newly diagnosed, MGMT-methylated malignant glioma. 24 patients were enrolled (23 GBM and one Grade III IDH-mutant astrocytoma), median age was 53.5 and mean KPS 91. ACZ was given on days 1-21 of each adjuvant TMZ cycle (250 mg BID days 1-7, increased to 500 mg BID days 8-21). No patient experienced the primary outcome of regimen limiting toxicity (RLT) and there were only three grade III adverse events deemed likely unrelated to ACZ. For the secondary endpoints of overall and progression free survival (OS and PFS, respectively), only the 23 GBM patients were included (22 IDH-wildtype and 1 IDH-mutant). From diagnosis, median PFS was 18.8 months (95% CI: 10.4-23.0) and median OS was 25.0 months (95% CI: 19.9-28.4). Median time from diagnosis to consent was 2.9 months. As of April 2021, only 7 of 23 deaths had occurred. 2-year OS% was 68.2%. Further analysis of secondary endpoints including 6-month objective response rate (ORR) and biomarker analysis of BCL-3 by IHC will be available in the coming months. In sum, the data indicate that addition of ACZ to TMZ is safe and does not lead to reduced TMZ dosing. Also, compared to historical data, interim outcomes suggest that addition of ACZ may substantially improve PFS and 2-year overall survival. These findings support the hypothesis that ACZ acts as a chemosensitizer of alkylating chemotherapy in GBM and support examination of this regimen in a randomized, placebo-controlled study.